Photoelectrochemical Properties of Ag/TiO2 Electrodes Constructed Using Vertically Oriented Two-Dimensional TiO2 Nanosheet Array Films. Issue 3 (1st January 2016) - Yang, Lei; Chu, Delin; Chen, Yu; Wang, Weihua; Zhang, Qianghua; Yang, Jinghong; Zhang, Miao; Cheng, Yunlang; Zhu, Kerong; Lv, Jianguo; He, Gang; Sun, Zhaoqi
Abstract : Vertically oriented two-dimensional TiO2 nanosheet (TNS) array films with dominant 001 facets decorated with Ag nanoparticles were synthesized on fluorine-doped tin oxide (FTO) by hydrothermal treatment and a successive ionic layer adsorption reaction (SILAR) technique. The amount of Ag nanoparticles on the TNS array surface can be controlled by changing the silver nitrate (AgNO3 ) solution concentration. The morphology, microstructure, optical, and photoelectrochemical properties of the Ag/TNS films were investigated in detail. The Ag/TNS films sensitized with five SILAR cycles showed the best photoelectrochemical properties and exhibited higher exciton separation efficiency. These excellent properties can be attributed to in situ growth of TNS with high energy 001 facets on FTO combined with surface plasmon resonance (SPR) of Ag nanoparticles.